ANTIDIABETIC ACTIVITY TEST OF ETHANOL EXTRACT OF YELLOW PUMPKIN LEAVES (Cucurbita moschata) ON MALE WHITE RATS (Rattus norvegicus) - Tamahiwu, Natasya Ester Rebeca; Bodhi, Widdhi; Datu, Olvie Syenni; Fatimawali , Fatimawali (UNIVERSITAS SAM RATULANGI, 2024)
Pumpkin is a plant that contains many natural phenolic compounds, making it potential as an antioxidant, antidiabetic and antihyperglycemic. The aims of this study was to determine the antidiabetic activity of ethanol extract of pumpkin leaves on blood glucose levels and body weight on male white rats induced by alloxan at a dose of 120 mg/kgBW. The type of research used in this study was an experimental laboratory using the pre test and post test with control group design methods. Rats was divided into 5 groups, each group consisting of 3 rats. Group I as the positive control was given metformin, group II as the negative control was given 0,5% CMC Na, groups III, IV and V as the treatment group were given extract doses of 150 mg/kgBW, 300 mg/kgBW, and 600 mg/kgBW. The results showed that the ethanol extract of pumpkin leaves had a significant effect on decreasing blood glucose levels of rats P(< 0,05) and had no significant effect on the body weight of rats P(> 0,05) and the dose of the extract was the best in reducing glucose levels blood of rats is a dose of 600 mg/kgBW